Hepatitis B Virus Pregenomic RNA Reflecting Viral Replication in Distal Non-tumor Tissues as a Determinant of the Stemness and Recurrence of Hepatocellular Carcinoma - Xiao, Yiwei; Cao, Junning; Zhang, Ze; Zeng, Chaoting; Ou, Guomin; Shi, Jihang; Liu, Zhixiu; Li, Yi; Deng, Juan; Xu, Yinzhe; Zhang, Wenwen; Li, Jie; et al. (Frontiers in Microbiology, 2022)
Background: The existence of hepatic cancer stem cells (CSCs) contributes to chemotherapy resistance and cancer recurrence after treatment or surgery. However, very little is known about the hepatitis B virus (HBV) replication and its relationship with the stemness of hepatocellular carcinoma (HCC) in HBV-related HCC patients. Methods: We collected tumor tissues (T), matched adjacent non-tumor tissues (NT) and distal non-tumor tissues (FNT) from 55 HCC patients for analysis. Results: We found HBV DNA levels were higher in T samples than NT and FNT samples, but HBV pgRNA and total RNA expressed lower in T samples. HBV pgRNA and total RNA correlates to HBV DNA among the T, NT and FNT samples. Further evidence for HBV replication in T samples was provided by HBV S, reverse transcriptase and X genes sequencing, showing that HBV sequences and genotypes differed between T and matched NT and FNT samples. HBV pgRNA and total RNA showed more frequent significant correlations with CSCs markers in NT samples in HBsAg-positive patients. The markers CD133 and OCT4 expressed higher in FNT samples, and HBV replication marker of pgRNA levels was significantly positively correlated to these two markers only in FNT samples. The detection of pgRNA and OCT4 in FNT was correlated to the recurrence of HCC in the resection of HCC patients. Analysis of HBV receptor, sodium taurocholate co-transporting polypeptide (NTCP), showed that NTCP was correlated negatively to CSCs markers in T samples, excepted for the CD44. Conclusions: HBV replication may present in HCC with a weak transcriptomic signature. Moreover, the expression level of HBV pgRNA in distal non-tumor tissues is a sensitive marker for HBV replication and prognosis, which is associated with CSCs related markers especially with OCT4 in distal non-tumor tissues and recurrence of HCC in HBV related HCC patients.